Use of intrauterine shunts in fetal surgery - Muñoz Acosta, Jairo (2024)
Since the 1960s, fetal medicine has evolved rapidly. Thanks to advances in technologyand the training of experts in this branch of medicine, it has become possible tomake more accurate diagnoses of fetal pathologies. Most of these pathologies can betreated postnatally. However, in some cases prenatal intervention is required sinceotherwise the pregnancy may culminate in fetal death or serious sequelae in thenewborn. Intrathoracic pathologies with mediastinal compression, aortic stenosis,lower urinary obstruction, congenital diaphragmatic hernia, myelomeningocele,lower urinary obstruction, intrauterine intravascular transfusion, fetus-fetaltransfusion syndrome and TRAP sequence, among others, are the fetal pathologiessusceptible to in-utero therapy. The present article refers to the use of intrauterineshunts in fetal surgery.